The Influence of Competency, SOP, and Information Technology on Employee Performance in Using the Ideaprocs Application in BUMD - Saepul Rizal; Amir Tengku Ramly; M. Aziz Firdaus; Nandang Sutisna; Rasiban Rasiban (Indonesian Interdisciplinary Journal of Sharia Economics (IIJSE), 2025)
Human resources (HR) are very much needed in this increasingly advanced modern era, employees play an important role in running the system in the company which includes the company's vision, mission, and goals. HR also plans and acts actively in all Company functions related to technological progress and advancement. The purpose of this study is to analyze "The Effect of Competence, SOP, and Information Technology on Employee Performance in Using the IdeaProcs Application in BUMD". The research method used is a quantitative research method using a purposive technique as a method of determining the sample based on certain considerations to determine a sample of 61 employees and distribute questionnaires using Google form and analyze using number processing software. The results of the study based on the results of the analysis using number processing software that the significance value is 0.000 <0.05 and the calculated F value is 46.502> F table 2.77, so it can be concluded that there is a significant influence of the Competence variables (X1), SOP (X2) and Information Technology (X3) simultaneously on Employee Performance (Y) of 71.0%.